Assessing Pre-Service English Teachers’ Folkloric-based Readings through Their Online Reading Accessibility - Didik Rinan Sumekto; Taufiqulloh Taufiqulloh; Theresia Dwi Widiastuti; Utami Budi Atri; Dylan Irdianza (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study attempts at assessing pre-service English teachers’ (PSETs’) informational, substantial, and contextual materials through the online selected folkloric-based readings—Lutung Kasarung and Calon Arang. It bridges the distinctive challenges through PSETs’ reading habit, reading effectiveness, and reading for pleasure accessibility. This study used the quantitative method by involving 248 sophomores and juniors PSETs at a private university in Yogyakarta, Indonesia. Data collection used simple random sampling through Likert scale’s self-rated questionnaire. The Respondents were 47 (19%) males and 201 (81%) females, ranged in between 19 to 22 years old (Mage = 20.50; SD = 2.769). Data analysis used descriptive statistics, chi-square test, and factor analysis to reveal PSETs’ online reading accessibility. Reading habit was very accomplishable with 41.1% respondents, whereas reading effectiveness was accomplishable with 63.7% respondents, and reading for pleasure was accomplishable with 56.5% respondents. Pearson corelations showed positive and significant relationships toward reading predictors (r = .902, n = 248, p < .000), Kaiser Meyer-Olkin was .688 exceeding .6 as confirmed, and Bartlett’s Sphericity test (df = 3; p = .000) statistically showed significant results with correlational matrix factorability. Further, principal components analysis indicated the proximity of three folkloric-based online reading predictors outreaching Eigenvalue’s square root (86%; 11%; 2.9%) with coherent interpretation. Reading habit shows the highest gain, creates literacies, elaborates ideas to reading accessibility, and triggers sense of positive and meaningful self-awareness relating to PSETs’ reading proficiencies, critical thinking, and verbal fluencies. The folkloric-based online readings accomplish PSETs’ affordability with the applicable digital technology for engaging their reading accessibility.